Comparison of Time-Resolved and First-Pass Contrast-Enhanced MR Angiography in Pretherapeutic Evaluation of Spinal Dural Arteriovenous Fistulas - Mathur, S. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Different MRA techniques used to evaluate spinal dural arteriovenous fistulas offer unique advantages and limitations with regards to temporal and spatial resolution. The purpose of this study was to compare the efficacy and interobserver agreement of 2 commonly used contrast-enhanced spinal MRA techniques, multiphase time-resolved MRA and single-phase first-pass MRA, in assessment of spinal dural arteriovenous fistulas. MATERIALS AND METHODS: Retrospective review of 15 time-resolved and 31 first-pass MRA studies in patients with clinical suspicion of spinal dural arteriovenous fistula was performed by 2 independent, blinded observers. DSA was used as the reference standard to compare the diagnostic performance of the 2 techniques. RESULTS: There were 10 cases of spinal dural arteriovenous fistula in the time-resolved MRA group and 20 in the first-pass MRA group. Time-resolved MRA detected spinal dural arteriovenous fistulas with sensitivity and specificity of 100% and 80%, respectively, with 100% correct-level localization rate. First-pass MRA detected spinal dural arteriovenous fistulas with sensitivity and specificity of 100% and 82%, respectively, with 87% correct-level localization rate. Interobserver agreement for localization was excellent for both techniques; however, it was higher for time-resolved MRA. In 5 cases, the site of fistula was not included in the FOV, but a prominent intradural radicular vein was observed at the edge of the FOV. CONCLUSIONS: Multiphase time-resolved MRA and single-phase first-pass MRA were comparable in diagnosis and localization of spinal dural arteriovenous fistulas and demonstrated excellent interobserver agreement, though there were more instances of ambiguity in fistula localization on first-pass MRA.